A one step quantitative RT-PCR for detection of SARS coronavirus with an internal control for PCR inhibitors - Poon, Leo L.M (J Clin Virol, 2004)
In this study, we report a one step quantitative RT-PCR assay for severe acute respiratory syndrome (SARS) diagnosis. The overall detection rate for clinical samples collected from Days 1 to 9 of disease onset is 86.2% and the specificity of the assay is 100%. To detect false negative results due to PCR inhibitors or faulty RNA extraction, we have further modified this one step RT-PCR assay for simultaneous detection of severe acute respiratory syndrome (SARS) coronavirus (CoV) and 18S ribosomal RNA (rRNA) as an internal positive control.